2017
DOI: 10.1007/s00586-017-5069-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cervical sagittal alignment change following correction of thoracic and thoracolumbar Scheuermann’s kyphosis

Abstract: Our study suggests that SK is not a homogenous group of patients. Two patterns of pre- and post-operative CSA are demonstrated in TK and TLK groups. T1 slope is the most important parameter in determining pre-operative CSA and correlates with other regional anatomical parameters (TK and LL). Post-operative CSA adaptations also correlate with T1 slope post-operative changes. However, post-surgical T1 slope correlates with different parameters in the two SK groups (TK and PT in TK group; TLK, LL, and PT in TLK g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
3
5
0
1
Order By: Relevance
“…We identified that an increased TK was associated with an increased CL, while patients with a large TLK had less CL. This is similar to previous studies that also described increased Long-term follow-up of untreated Scheuermann's kyphosis 11 TK leading to an anteriorly projected cervical spine, whereas TLK was associated with a vertically oriented cervical spine [24]. Increased TK is associated with increased cSVA and CL, which may contribute to increased pain [25].…”
Section: Discussionsupporting
confidence: 90%
“…We identified that an increased TK was associated with an increased CL, while patients with a large TLK had less CL. This is similar to previous studies that also described increased Long-term follow-up of untreated Scheuermann's kyphosis 11 TK leading to an anteriorly projected cervical spine, whereas TLK was associated with a vertically oriented cervical spine [24]. Increased TK is associated with increased cSVA and CL, which may contribute to increased pain [25].…”
Section: Discussionsupporting
confidence: 90%
“…In terms of proximal alignment, T1S has been shown previously to be a predictor of overall cervical sagittal alignment. 21,22 The results of the present study support these previous findings and further suggest that among patients with PJK, there is a significant correlation between the degree of focal deformity (ie, PJA) and the T1S with an associated positive correlation with CL and anterior cervical or cervicothoracic sagittal alignment. This was irrespective of UT or LT UIV (Table 5).…”
Section: Discussionsupporting
confidence: 90%
“…They evaluated and compared the post-op cervical sagittal alignment in patients with thoracic and thoracolumbar Scheuermann's kyphosis. They found that the cervical lordosis increased in patients with thoracolumbar Scheuermann's kyphosis, whereas the patients with thoracic Scheuermann's kyphosis had a decrease in their cervical lordosis [20].…”
Section: Discussionmentioning
confidence: 99%